Classification and Analysis of Attritional Glenoid Bone Loss in Recurrent Anterior Shoulder Instability. (March 2017) - McNeil, John W.; Beaulieu-Jones, Brendin R.; Bernhardson, Andrew S.; LeClere, Lance E.; Dewing, Christopher B.; Lynch, Joseph R.; Golijanin, Petar; Sanchez, George; Provencher, Matthew T.
Background: Recognition and proper treatment of glenoid bone loss (GBL) are important for successful management of anterior shoulder instability. Although GBL has been described as the amount of bony loss from the front of the glenoid, there is also a fragment of bone that is usually displaced and often undergoes attrition. Thus, due to attritional bone loss (ABL) of the fragment, insufficient bone is left to fully reconstruct the glenoid. Purpose: To (1) evaluate ABL of the glenoid fragment in recurrent anterior shoulder instability and (2) correlate ABL with clinical history, fragment size, and radiographic findings. Study Design: Cross-sectional study; Level of evidence, 3. Methods: GBL was evaluated on 3-dimensional computed tomography (3D CT) en-face view and was measured as percentage loss. The bone fragment size was measured, and attrition of the fragment was determined by evaluation of the amount remaining relative to the initial defect; patients were stratified into minimal (<34%), moderate (34% to <67%), and severe (≥67%) attritional loss groups. Clinical history and demographics were correlated to ABL, and GBL and ABL were compared. Results: The overall median percentage GBL was 15.3% (interquartile range [IQR], 9.9%-20.0%), with a mean (±SD) percentage GBL of 16.5% ± 9.0%. Study participants had a corresponding median percentage ABL of 75.8% (IQR, 53.8%-95.7%) and a mean percentage ABL of 72.0% ± 24.4%. A total of 61.2% of patients (n = 85) exhibited severe ABL, while 30.2% had moderate ABL and 8.6% had minimal ABL. The total time of instability was significantly associated with percentage of attritional bone loss ( P < .05). In addition, the time of instability was greatest in patients in the third tertile of ABL (≥87.5%; P = .08). A significant difference was found in total time of instability among patients in the highest tertile of ABL (38.6 months) versus both the middle (26.7 months) and lowest (32.8 months) tertiles ( P < .05). Conclusion: The study results indicate that in the majority of patients with recurrent anterior instability, GBL presents with extensive attrition of the bone fragment independent of initial glenoid bone loss; therefore, surgeons should be cognizant that the remaining bone fragment is unable to reconstitute glenoid bone stock. In addition, the results showed more attritional bone loss in patients with a longer duration of instability symptoms, indicating a role for incorporating symptom duration in determining proper management.